The Students’ Common Grammatical Mistakes in Writing Argumentative Essay Through Impromptu Theme - Tahang, Heriyanti (Universitas Muhammadiyah Mataram, 2024)
The objective of the study was to discover the prevalent grammatical errors made by students in their English writing. This was done by analyzing impromptu essays written by seventh-semester students in the English language education program at the University of Muhammadiyah Sorong. The study utilized a descriptive qualitative research design. The study sample comprised 18 students in their seventh semester, recruited using purposive sampling. The research data were collected from the participants' argumentative essays, which served as the writing assessment centered around the theme,